Displaying the long-term progression of patients with coronary artery disease. Issue 5 (November 1995) - Sherlaw-Johnson, C.; Mitchard, J.; Gallivan, S.; Patterson, D. L.; Treasure, T.
Abstract : Cardiac clinicians are often faced with the problem of trying to assimilate details of a patient's long-term history. Case notes are often lengthy, making this process difficult if not impossible in the time available during an outpatient examination. A computer system has been developed to assist with this task. This generates a graphical summary of the principal features of a patient's long-term progression. It gives an overview of how the patient's anginal status has changed, his or her drug treatment and any surgical interventions. The system also allows the clinican to display summaries of diagnostic tests carried out. The system can be used to assist clinical management and speed up outpatient examination. It can also be used to facilitate case conference sessions and has potential for being used in medical education.